2006
DOI: 10.1007/s00330-005-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of hamstring injuries: therapeutic implications

Abstract: Though recent research into the diagnosis and management of hamstring disorders has resulted in early and accurate recognition of injury, hamstring strain remains the most common form of muscle injury in the active population. With prompt recognition of hamstring strain, an appropriate rest and rehabilitation routine may be devised by the sports clinician in the hope of avoiding future and possibly more debilitating injury. As such, imaging has played a pivotal role in assisting athletes, both elite and recrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 64 publications
3
59
0
2
Order By: Relevance
“…This, together with the capability to evaluate multiple anatomic planes, make it the most suitable technique to evaluate muscle injures [23][24][25][26]. Most muscle injuries might not require imaging, but as this noninvasive technology continues to improve and becomes even more commonplace, it can play a role in rehabilitation planning and prognosis [3].…”
Section: Discussionmentioning
confidence: 99%
“…This, together with the capability to evaluate multiple anatomic planes, make it the most suitable technique to evaluate muscle injures [23][24][25][26]. Most muscle injuries might not require imaging, but as this noninvasive technology continues to improve and becomes even more commonplace, it can play a role in rehabilitation planning and prognosis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging may not be necessary in all cases, and a thorough physical examination, including careful palpation, 3 can provide valuable information about the nature of the injury. 8 Nevertheless, imaging not only confirms the diagnosis of muscle injury but also supplies information that helps to predict the time to sport resumption in professional and recreational athletes.…”
Section: Discussionmentioning
confidence: 99%
“…9,14-17 Several groups 5,8,15 compared the performance of sonography and MRI. Among them, a prospective study 14 showed that sonography was as useful as MRI for assessing acute hamstring injury (48 injuries in our study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces symptoms of pain, and may improve healing time. It is most frequently performed for contusional injuries of the vasti muscles of the thigh, but has been used anecdotally at other sites, including the hamstrings [57]. Aspiration is ideally performed at about 10 days post injury, when the haematoma is in a stage of liquefaction and can be monitored by serial ultrasound imaging [7].…”
Section: Muscle Tearmentioning
confidence: 99%